2012
DOI: 10.1021/es203674n
|View full text |Cite
|
Sign up to set email alerts
|

DGT Measurement of Dissolved Aluminum Species in Waters: Comparing Chelex-100 and Titanium Dioxide-Based Adsorbents

Abstract: Aluminum is acutely toxic, and elevated concentrations of dissolved Al can have detrimental effects on both terrestrial and aquatic ecosystems. Robust analytical methods that can determine environmentally relevant Al fractions accurately and efficiently are required by the environmental monitoring community. A simple, robust passive sampling method, the diffusive gradients in thin films (DGT) technique, was evaluated for the measurement of dissolved Al species in freshwater and marine water using either Chelex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 52 publications
2
45
1
Order By: Relevance
“…The elution factors used in this study (except for Al) were those reported for the MBL by Panther et al [23]. In terms of Al, an elution factor of 0.845 (using an average of Chelex and Metsorb gels) was utilized [9].…”
Section: Sample Analysis and Methods Detection Limitsmentioning
confidence: 99%
See 4 more Smart Citations
“…The elution factors used in this study (except for Al) were those reported for the MBL by Panther et al [23]. In terms of Al, an elution factor of 0.845 (using an average of Chelex and Metsorb gels) was utilized [9].…”
Section: Sample Analysis and Methods Detection Limitsmentioning
confidence: 99%
“…Al(OH) 4 predominant at pH 8.30 (99%), the biggest change in speciation for all the elements studied (Table S1). Assuming the negatively charged Al(OH) 4 species are less hydrated than Al 3+ species, the size of the diffusing Al species at pH 8.30 is expected to be smaller than pH 4.01 [9]. Consequently, the D values measured for Al change substantially between pH 4.01 and 8.30 (a ratio of 0.73 with ODL and 0.77 with RDL), while the effect is less than 13% for all elements.…”
Section: Diffusion Coefficient Measurements Using Time-series Dgt Depmentioning
confidence: 99%
See 3 more Smart Citations